ELEMENTI STRATIGRAFICI E STRUTTURALI DELLA GALLERIA BELLANO - VARENNA (NUOVA SS 36) ( COMO) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Data obtained from the new road tunnel excavated between Bellano and Varenna (Como) are here summarized and compared with surface. Rocks penetrated are from the crystalline basement to the Calcare di Perledo - Varenna (Ladinian). Stratigraphically the sequence does not contain relevant new data. However, the uppermost conglomerate/sandstone unit is considered as independent from the Servino Fm. and a Lower Anisian age is suggested for. Concerning tectonics, the sedimentary cover is interpreted, on the whole, as stratigraphically continuous on the crystalline basement and cutted by late strike-slip faults. The gravity sliding evidences are scanty in the considered area.
Keywords: Stratigraphy; tectonic; Permian; Triassic; Southern Alps; Italy.